A survey of icephobic coatings and their potential use in a hybrid coating/active ice protection system for aerospace applications. (February 2019) - Huang, Xiao; Tepylo, Nick; Pommier-Budinger, Valérie; Budinger, Marc; Bonaccurso, Elmar; Villedieu, Philippe; Bennani, Lokman
Abstract: Icephobic coatings for aircraft and other surfaces subjected to ice accretion have generated great interest in the past two decades, due to the advancement of nanomaterials, coating fabrication methods, biomimetics, and a more in-depth understanding of ice nucleation and ice adhesion. Icephobic coatings have demonstrated the ability to repel water droplets, delay ice nucleation and significantly reduce ice adhesion. Despite these ongoing research activities and promising results, the findings reported hereafter suggest that coatings alone cannot be used for aircraft anti-icing and de-icing operations; rather, they should be considered as a complementary option to either thermal or mechanical ice protection methods, for reducing power consumption and the ecological footprint of these active systems and for expediting ground de-icing operations. This paper will first review the state-of-the-art of icephobic coatings for various applications, including their performance and existing deficiencies. The second part of this paper focuses on aerospace anti-icing and de-icing requirements and the need for hybrid systems to provide a complete ice protection solution. Lastly, several urgent issues facing further development in the field are discussed. Graphical abstract: Image 1